Oil spill treatment using treated peat / Imran Ismail - Ismail, Imran (2000)
The use of treated peat for oil spill treatment is not a new discovery. There are several companies in the world were involved in the production of treated peat. As we already know, peat is one of the carbonaceous materials that can used to produce charcoal and activated carbon. The production of a treated peat (charcoal and treated charcoal) by using muffle furnace available at UiTM laboratory was done. Two samples of peat were prepared. A raw peat was placed in the porous ceramic. The chemical used in this research is Hydrochloric acid (HCl) - for impregnation purpose. Charcoal was produced by carbonized it in the muffle furnace by means of porous ceramic as burning medium. Treated charcoal was prepared by impregnating the charcoal produced in early step with 3 M HCl. This was done to compare the effectiveness (adsorption characteristics) of each method. Muffle furnace is use to burn the samples at high temperature (at least 550°C). Then the product was undergone quality tests to determine their porosity. The tests are Methylene Blue Decolorizing Power and lodine Value. Then, the product was tested on crude petroleum, which is spread at the surface of water. The crude petroleum was supplied by PETRONAS.